THE ANALYSIS OF THE EFFECT OF FDR, NPF, AND DPK ON PROFIT-SHARING-BASED MUDHARABAH FINANCING IN BANKS SHARIA IN INDONESIA PERIOD 2012-2018 - Ferri Alfadri; Muhammad Arif; Ticha Lubis; taufik taufik (Journal Of Sharia Banking, 2023)
This research is motivated The background in this study is the occurence of variable mudharabah financing fluctuations in 2012-2018 in islamic banking. The formulation of the problem in thid study is whether there is an influence of financing to deposit ratio, non performing financing, and third party funds on profit-sharing based mudharabah financing in islamic banking in indonesia in 2012-2018. This study aims to determine the effect of FDR, NPF, and DPK on Mudharabah financing in Islamic Banking, which consist of islamic commercial banks and islamic business units in Indonesia. This research is quantitative research with secondary data. The sample in study used a saturated sampling technique. The number of samples is 84 samples. Data analysist method used in this research is descriptive statistical analysis, normality test, classic assumption test consisting of multicolinearity test, heteroscedasticity test, autocorrelation test, then hypothesis testing and multiple linear regression tests. Based on the partial test result (t test) showed that FDR affected mudharabah financing, then NPF variable influenced mudharabah financing, and DPK variable influenced mudharabah financing then Anova test (F test) simultaneously the FDR, NPF, and DPK variables had a positive effect on mudharabah financing.